PEMINDAHAN IBU KOTA DAN POTENSI KONEKTIVITAS PEMERATAAN EKONOMI - Taufiq, Muhammad (UI Scholars Hub, 2020)
Along with the development of understanding about the discourse of the relocation of Indonesia's capital city by existing studies, one of the various positive potentials to be obtained from this policy is the realization of the connectivity of economic equality. In addition to balancing regional development, the new location's connectivity should be as capable as possible in creating economic equality concerning its archipelagic concept of country. It is undeniable that Indonesia's economy is centered on Java island, especially around the Jakarta capital city, with a very high level of development as a center of national scale growth, far beyond the other large islands such as Sumatra, Kalimantan, Sulawesi, and Papua. In creating a more equitable economic growth, the relocation of the capital city should as much as possible refer to economic connectivity as a trigger in improving the economy of the large islands in Indonesia. A question arises how the potential of connectivity of economic equality in the context of relocation of Indonesia's capital city. The article aims to present a literature study producing an understanding regarding this matter for the consideration of stakeholders in decision making. This study uses a descriptive and evaluative method with secondary data sources such as scientific journals, literature books, and internet news. Its result confirms the existence of an opportunity to create economic equality through the policy of the capital city relocation with the assumption that new growth centers of national scale will emerge outside Java. The flow of migration, investment, internal connectivity, and external connectivity are the elements making this happen.